2014
DOI: 10.1177/0091026014549473
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Performance Management

Abstract: Identity and identification are root constructs in organization studies. Identity provides an interpretive framework with which to evaluate the appropriateness of behavior, and as such, in organizations the construct has a fundamental relationship with employee performance. This study develops a theoretical framework linking identification to change-oriented behavior, a type of extra-role activity aimed at introducing micro-level organizational change in order to improve long-term performance and efficiency. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 172 publications
(440 reference statements)
0
4
0
Order By: Relevance
“…As a psychological response to management practices, employees who engage in their work may develop an active pro-organizational behavior such as OCB (Harrison et al, 2006; Shrotryia et al, 2022). Furthermore, engagement may enhance the perception of identification with one’s organization among public employees (Campbell, 2015; Miao et al, 2019). For instance, Saks (2006) demonstrated that employee engagement increases OCB because of their psychological ownership shaped by active participation at work.…”
Section: Relevant Literature and Hypothesesmentioning
confidence: 99%
“…As a psychological response to management practices, employees who engage in their work may develop an active pro-organizational behavior such as OCB (Harrison et al, 2006; Shrotryia et al, 2022). Furthermore, engagement may enhance the perception of identification with one’s organization among public employees (Campbell, 2015; Miao et al, 2019). For instance, Saks (2006) demonstrated that employee engagement increases OCB because of their psychological ownership shaped by active participation at work.…”
Section: Relevant Literature and Hypothesesmentioning
confidence: 99%
“…In the context of this research, the structural network refers to the community, while the relational dimension is the kinship that occurs in organizations. Social capital is one way to conceptualize social relationships in the workplace, and this study develops a turnover intentions model based on social capital (Campbell, 2015). Social capital is an intangible part of an organization's assets that must be maintained and developed for competitive advantage (Andrews, 2010; Nahapiet and Goshal, 1998).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Third, in 40% of the reviewed correlations, OCB was measured as a generalized construct or, in other words, as a composite measure [13,32]. In 19% of cases, the OCB types were the subjects of differentiated measurement, for example, OCB-I and OCB-O [10,33], or AOB and COB [14,34]. In other cases, specific OCB manifestations were assessed, e.g., courtesy and sportsmanship [26], helping behavior [16], civic virtue [35], voice behavior [36] and taking charge [22].…”
Section: Relationship Between the Dimensions Of Identification And Ocb 121 Gaps In The Study Of Id-ocb Connectionsmentioning
confidence: 99%
“…In large and even medium-sized organizations, the following structural levels can easily be recognized: (1) the organization as a whole, which can be either an independent unit (for example, a higher education institution) or a subsidiary (a branch) of a large corporation; (2) the secondary-level structural unit or division (for example, a department within a university or a specific manufacturing facility within a company); (3) a small group, i.e., a basic-level structural unit, which is usually included in a secondary-level unit (for example, a laboratory within a university department or a self-regulating small work group in a manufacturing facility). These structural units serve as identification foci, and employees accordingly develop organizational identification (organizational ID/OID) [12,13], sub-organizational identification (sub-organizational ID/SoID) [14,15], or group identification (group ID/GID) [16,17].…”
Section: Introductionmentioning
confidence: 99%